Comparison of surgical, functional, and oncological outcomes of open and robot-assisted partial nephrectomy - Ugur Boylu; Cem Basatac; Umit Yildirim; Fikret F Onol; Eyup Gumus (Journal of Minimal Access Surgery, 2015)
Background: We aimed to compare the surgical, oncological, and functional outcomes of robot-assisted partial nephrectomy (RAPN) with open partial nephrectomy (OPN) in the management of small renal masses. Materials and Methods: Between 2009 and 2013, a total of 46 RAPN patients and 20 OPN patients was included in this study. Patients′ demographics, mean operative time, estimated blood loss (EBL), warm ischemia time (WIT), length of hospital stay, pre- and post-operative renal functions, complications and oncological outcomes were recorded, prospectively. Results: Mean tumor size was 4.04 cm in OPN group and 3.56 cm in RAPN group (P = 0.27). Mean R.E.N.A.L nephrometry score was 6.35 in OPN group and 5.35 in RAPN group (P = 0.02). The mean operative time was 152 min in OPN group and 225 min in RAPN group (P = 0.006). The mean EBL in OPN and RAPN groups were 417 ml and 268 ml, respectively (P = 0.001). WIT in OPN group was significantly shorter than RAPN group (18.02 min vs. 23.33 min, P = 0.003). The mean drain removal time and the length of hospital stay were longer in OPN group. There were no significant differences in terms of renal functional outcomes and postoperative complications between groups. Conclusion: Minimally invasive surgical management of renal masses with RAPN offers better outcomes in terms of EBL and length of stay. However, the mean operative time and WIT were significantly shorter in OPN group. RAPN is a safe and effective minimally invasive alternative to OPN in terms of oncological and functional outcomes.